High-Intensity Exercise Induced Changes in Oxidative Stress and Skeletal Muscle Damage in Male Endurance and Resistance Trained Athletes: A Comparative Study - Debdatta Saha; Tamalica Hore; Debajyoti Mukherjee; Ananda Kisor Pal; Santiranjan Dasgupta; Rubia Mondal; Amit Bandyopadhyay (Exercise Medicine, 2026)
Objectives: High-intensity exercise (HIE) can induce skeletal muscle damage and oxidative stress not only in sedentary individuals but also in trained athletes. This study aimed to evaluate and compare oxidative stress levels and muscle damage markers following high-intensity exercise among male resistance-trained athletes (RA, n = 18), endurance-trained athletes (EA, n = 18), and sedentary controls (SC, n = 30) aged 20–30 years.Methods: A familiarization trial was performed for each participant to determine the treadmill speed and inclination that elicited 80% of maximal heart rate (HRmax). Fasting blood samples were collected and resting physiological and physical parameters were measured before the exercise trial. Participants then performed exercise at 80% HRmax until volitional exhaustion. Blood samples were collected again immediately after exercise and 48 hours after the exercise trial.Results: Skeletal muscle damage and inflammatory markers, including creatine kinase (CK), lactate dehydrogenase (LDH), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and C-reactive protein (CRP), increased significantly after exercise and remained elevated at 48 h in all groups (p < 0.05). Superoxide dismutase (SOD) and catalase (CAT) activities increased after exercise and remained above pre-exercise levels at 48 h, whereas total thiol concentrations decreased after exercise and remained below pre-exercise levels at 48 h. Lipid peroxidation (LPO) increased immediately after exercise but decreased during recovery. The SC group showed significantly lower AST, ALT, and LPO values than the athletic groups at all time points (p < 0.05). Several oxidative stress and muscle damage markers remained altered 48 h after exercise, indicating incomplete recovery within the observation period. No significant differences were observed between the RA and EA groups in any of the measured parameters at any time point.Conclusions: HIE induced changes in muscle damage and oxidative stress markers in both sedentary controls and trained athletes. However, most oxidative stress and muscle damage responses did not differ significantly between resistance-trained and endurance-trained male athletes.